Veterinary clinical procedures in large animal practice - Rockett, Jody (Thomson Delmar Learning, 2007)
This is a step-by-step procedural manual that addresses the most common clinical procedures used with horses, cattle, llamas, goats, and pigs, with primary emphasis placed on horses and cattle. The text features the purpose, potential complications, and a detailed equipment list for every procedure and lists the technical steps of each procedure. It also includes a rationale column which explains, amplifies, or provides additional insight concerning each step. Topics include restraint; husbandry; physical examination; specimen collection; clinical procedures; lower limb radiographs; neonatal procedures; and surgical and anesthetic preps. The appendices contain values such as normal temperature, pulse and respiration rates, clinical chemistry, conversions, CBC, and centesis values. Common vernacular and terminology concerning animal husbandry and gestation times are also provided.